MEASURING SERVICE QUALITY USING THE SERVQUAL METHOD AND ITS IMPLICATIONS FOR CORPORATE BRANDING OF PT. PROLAB MEDIKA SERANG CITY: PENGUKURAN KUALITAS PELAYANAN MENGGUNAKAN METODE SERVQUAL SERTA IMPLIKASINYA TERHADAP CORPORATE BRANDING PT. PROLAB MEDIKA KOTA SERANG - Hafidz Hanafiah (Yayasan Education and Social Center, 2022)
In this study, it used Mix-Methods, which is a combination of quantitative and qualitative. Quantitative measurement of service quality using the Service Quality or SERVQUAL method, while the implications for corporate branding use qualitative. The results showed that customer satisfaction about service quality was still below 80% or 75.90%. The numbers that need to be improved again in the future for the sustainability of corporate branding in the customer perspective